2004
DOI: 10.1073/pnas.0403033101
|View full text |Cite
|
Sign up to set email alerts
|

The linker-loop region ofEscherichia colichaperone Hsp31 functions as a gate that modulates high-affinity substrate binding at elevated temperatures

Abstract: Precise control of substrate binding and release is essential for molecular chaperones to exert their protective function in times of stress. The mechanisms used are diverse and have been difficult to unravel. Escherichia coli heat-shock protein 31 (Hsp31) is a recent addition to the known complement of eubacterial chaperones. Crystallographic studies have revealed the presence of a hydrophobic bowl at the Hsp31 dimer interface and shown that the linker region connecting the two structural domains within each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 20 publications
1
26
0
2
Order By: Relevance
“…In agreement with crystallographic and biochemical data showing that Hsp31 relies on structural rearrangements as part of its mechanism of action at high temperatures, 18,19 we found that, although native Hsp31 was fairly resistant to degradation by PK at 37 C, its susceptibility to proteolysis was greatly increased at 45 C [ Fig. 6(A)].…”
Section: Influence Of His-tagging On Hsp31 Structuresupporting
confidence: 76%
See 4 more Smart Citations
“…In agreement with crystallographic and biochemical data showing that Hsp31 relies on structural rearrangements as part of its mechanism of action at high temperatures, 18,19 we found that, although native Hsp31 was fairly resistant to degradation by PK at 37 C, its susceptibility to proteolysis was greatly increased at 45 C [ Fig. 6(A)].…”
Section: Influence Of His-tagging On Hsp31 Structuresupporting
confidence: 76%
“…were diluted into refolding buffer containing no additive or supplemented with a sixfold molar excess of clHsp31, His 6 -Hsp31, or Hsp31-His 6 at 23 C. Like native Hsp31, 13,19 cl-Hsp31 improved the recovery of active MDH by twofold and that of CS by sevenfold [ Fig. 2(A)].…”
Section: Influence Of His-tagging On Hsp31 Chaperone Activitymentioning
confidence: 99%
See 3 more Smart Citations